Fibroblast-like synoviocytes-dependent effector molecules as a critical mediator for rheumatoid arthritis: Current status and future directions. (2nd January 2017) - Ganesan, Ramamoorthi; Rasool, Mahaboobkhan
ABSTRACT: Rheumatoid arthritis (RA) is a systemic-autoimmune-mediated disease characterized by synovial hyperplasia and progressive destruction of joint. Currently available biological agents and inhibitor therapy that specifically target tumor necrosis factor-α, interleukin 1β (IL-1β), IL-6, T cells, B cells, and subcellular molecules (p38 mitogen-activated protein kinase and janus kinase) cannot facilitate complete remission in all patients and are unable to cure the disease. Therefore, further potent therapeutic targets need to be identified for effective treatment and successful clinical outcomes in patients with RA. Scientific breakthroughs have brought new insights regarding fibroblast-like synoviocytes (FLS), a major constituent of the synovial hyperplasia. These play a pivotal role in RA invading cartilage and bone tissue. Currently there are no effective therapies available that specifically target these aggressive cells. Recent evidences indicate that FLS-dependent effector molecules (toll-like receptors, nodal effector molecules, hypoxia-inducible factor, and IL-17) have emerged as important mediators of RA. In this review, we discuss the pathological features and recent advances in understanding the role of FLS-dependent effector molecules in the disease onset of RA. Pharmacological inhibition of FLS-dependent effector molecules might be a promising option for FLS-targeted therapy in RA.